Accumulated soil seed bank of the invasive sand dropseed (Sporobolus cryptandrus) poses a challenge for its suppression - Török Péter; Espinoza Ami Francis David; Tóth Katalin; Diaz Cando Patricia Elizabeth; Guallichico Suntaxi Luis Roberto; McIntoshné Buday Andrea; Hábenczyus Alida Anna; Törő-Szijgyártó Viktória; Kovacsics-Vári Gergely; Tölgyesi Csaba; Tóthmérész Béla; Sonkoly Judit (2024)
Global warming, elevated atmospheric CO 2 concentrations and increased likeliness of extreme drought and wildfires in many regions will likely favour C4 grass species. To support future management actions, we explored the effect of the encroachment of an invasive perennial C4 grass, Sporobolus cryptandrus on the composition of soil seed banks in dry sand grasslands in Central Europe. In five mass‐locality sites of the species we assessed the composition and vertical segmentation of the soil seed bank in 12 1‐m 2 plots along an increasing cover of the invasive species. We found that the seed bank diversity and density decreased with increasing sampling depth; the decrease in density was affected by the increasing S. cryptandrus cover. Neither the diversity nor the seed bank density of other species were affected by increasing S. cryptandrus cover but both were affected by the sampling site. Most of the studied seed bank characteristics were affected by the sampling depth, but none of them were affected by the increasing cover of S. cryptandrus . Increasing cover of S. cryptandrus in the vegetation was associated with an increasing proportion of S. cryptandrus seeds in the seed bank, and we found a low‐density soil seed bank of the species even in plots with no S. cryptandrus cover. Our finding that S. cryptandrus forms a massive soil seed bank, together with the predicted decrease in the precipitation of the summer months and increase in the frequency of droughts in the region, projects further rapid spread of the species.
Keywords: Biológiai tudományok